Improvement in Zebrafish with Diabetes and Alzheimer's Disease Treated with Pasteurized Akkermansia muciniphila - Qu, Linkai; Liu, Fan; Fang, Yimeng; Wang, Lei; Chen, Haojie; Yang, Qinsi; Dong, Hao; Jin, Libo; Wu, Wei; Sun, Da (Microbiology spectrum, 2023)
The interaction between intestinal microflora and host affects the progression of diabetes and Alzheimer's disease. As a recognized next-generation probiotic, Akkermansia muciniphila has been shown to play a key role in the progression of diabetes and Alzheimer's disease, but whether A. muciniphila can improve diabetes complicated with Alzheimer's disease and its potential mechanism are unclear. Diabetes and Alzheimer's disease (AD) are associated with specific changes in the composition of the intestinal flora. Studies have shown that the supplementation with pasteurized Akkermansia muciniphila has therapeutic and preventive effects on diabetes. However, it is not clear whether there is any association with improvement in and prevention of Alzheimer's disease and diabetes with Alzheimer's disease. Here, we found that pasteurized Akkermansia muciniphila can significantly improve the blood glucose, body mass index, and diabetes indexes of zebrafish with diabetes mellitus complicated with Alzheimer's disease and also alleviate the related indexes of Alzheimer's disease. The memory, anxiety, aggression, and social preference behavior of zebrafish with combined type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (TA zebrafish) were significantly improved after pasteurized Akkermansia muciniphila treatment. Moreover, we examined the preventive effect of pasteurized Akkermansia muciniphila on diabetes mellitus complicated with Alzheimer's disease. The results showed that the zebrafish in the prevention group were better in terms of biochemical index and behavior than the zebrafish in the treatment group. These findings provide new ideas for the prevention and treatment of diabetes mellitus complicated with Alzheimer's disease. IMPORTANCE The interaction between intestinal microflora and host affects the progression of diabetes and Alzheimer's disease. As a recognized next-generation probiotic, Akkermansia muciniphila has been shown to play a key role in the progression of diabetes and Alzheimer's disease, but whether A. muciniphila can improve diabetes complicated with Alzheimer's disease and its potential mechanism are unclear. In this study, a new zebrafish model of diabetes mellitus complicated with Alzheimer's disease was established, and the effect of Akkermansia muciniphila on diabetes mellitus complicated with Alzheimer's disease is discussed. The results showed that Akkermansia muciniphila after pasteurization significantly improved and prevented diabetes mellitus complicated with Alzheimer's disease. Treatment with pasteurized Akkermansia muciniphila improved the memory, social preference, and aggressive and anxiety behavior of TA zebrafish and alleviated the pathological characteristics of T2DM and AD. These results provide a new prospect for probiotics in the treatment of diabetes and Alzheimer's disease.